The Philosophy and Psychology of Music Perception : a discussion of the communicative power of music and its relationship with the written word - Philips, Beatrice (Sibelius-Akatemia, 2011)
During this discussion I want to explore the mystery of expressive music and find out what it is that makes us feel we have experienced some kind of emotional 'message' from the composer. In the same way that literature and words can instantly conjure up an emotion in the reader - through relaying an idea or a story or by simply using beautiful language - music can cause the listener to feel an immediate emotional response. I want to explore whether this means that music itself can be classified as a type of 'language', since it is undeniably a 'communicator' of sorts. To find some answers to this I have found it important to look at the two 'languages' used together - Is music reliant, for example, on the written word - or discursive language - for it to hold any powerful meaning or create any real emotional response from the listener? In other words, is music with a literal programme or story attached to it more expressive? Musical philosopher Susanne Langer's thoughts on this subject will be explored and those of Deryck Cooke. I will also discuss Hans Keller's views on the power of music as a communicator - Keller believed that words are completely unnecessary when discussing music, and illustrates this through "Functional Analysis". It is of course also necessary to look at many examples of both programme music and "pure" music with no literal story attached - and compare what each are 'saying' and how successful their messages are.
Keywords: Beethoven, Ludwig van.; filosofia; psykologia; fi=sävellys ja musiikinteoria|sv=komposition och musikteori|en=Composition and Music Theory|